2022
DOI: 10.3390/su141811628
|View full text |Cite
|
Sign up to set email alerts
|

African Indigenous Female Entrepreneurs (IFÉs): A Closed-Looped Social Circular Economy Waste Management Model

Abstract: Uncontrolled waste disposal sites remain prevalent in low- and lower-middle-income countries, with organic waste constituting between 50 and 80% of the total openly dumped waste volumes. Waste-to-wealth initiatives focused on biowaste enterprises through female entrepreneurs can advance the eradication of open dumps while creating economic opportunities. This study, therefore, proposes an organizational model that leverages Indigenous female institutions, circular economy concepts, and a closed-loop biowaste m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
2
6
0
Order By: Relevance
“…This study aligned with the studies of Smitskikh, Titova, and Shumik [64] and Chineme, Assefa, Herremans, Wylant, and Shumo [71], who identified that circular economy-related strategy, waste reduction, reuse, and recycling, facilitate collaboration embedded in circular social enterprise. These are widely being applied by Company X, as seen in Section 5.…”
Section: Circular Social Entrepreneurship and Business Modelssupporting
confidence: 85%
See 1 more Smart Citation
“…This study aligned with the studies of Smitskikh, Titova, and Shumik [64] and Chineme, Assefa, Herremans, Wylant, and Shumo [71], who identified that circular economy-related strategy, waste reduction, reuse, and recycling, facilitate collaboration embedded in circular social enterprise. These are widely being applied by Company X, as seen in Section 5.…”
Section: Circular Social Entrepreneurship and Business Modelssupporting
confidence: 85%
“…Smitskikh, Titova, and Shumik [64] found that waste reduction, reuse, and recycling, as well as the use of renewable energy sources and the design of products and services that are sustainable and environmentally friendly, were identified as some of the circular economy principles implemented by social enterprises. Similar evidence was found by Chineme et al [71], who mentioned that key circular economy-related strategies were included, such as waste as a resource, facilitating collaboration and cultural appreciation through co-production, incorporating the selforganization skills of a minority group, and using a simple waste management technique generating value from black soldier fly larvae for fish and animal feed production.…”
Section: Social Enterprise and Cbmsupporting
confidence: 77%
“…This will potentially improve their working and economic conditions since current waste collection activities are carried out with few health and safety measures. Careful public policies must be also directed toward supporting female entrepreneurs within the circular economy, such as farmers adopting the use of compost from the plant or those within the recycling industries [93].…”
Section: Broad Circular Economy Framework For Gamamentioning
confidence: 99%
“…A similar scoping review found that "50.7% of all studies linking pollution and IPs [Indigenous peoples] have been conducted among only 15 different Indigenous groups" with nearly half in North America (Fernández-Llamazares et al, 2020, p. 325). Another potential reason for the skew is that in the Global south, especially in Asia and Africa, the term "Indigenous" is not common or is rejected outright at the community and/or state level (Chineme et al, 2022;Senekane et al, 2022).…”
Section: The Corpusmentioning
confidence: 99%